1989
DOI: 10.3109/02713688909025807
|View full text |Cite
|
Sign up to set email alerts
|

Purification of aldehyde oxidase from bovine ciliary body

Abstract: Ocular aldehyde oxidase was purified for the first time from bovine ciliary body cytosol by ammonium sulfate fractionation and successive HPLC using DEAE anion-exchange and hydroxyapatite columns. The purified enzyme was homogeneous by the criterion of sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The molecular weight of the enzyme was estimated to be about 150,000 by electrophoresis and to be about 300,000 by gel filtration HPLC on a TSK gel G3000SWXL column, indicating that the enzyme consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…AO distribution in other tissues is highly species dependent. For example, in mouse AO activity in lung tissue is more significant than in the rat. The distribution of AO at the cellular level has also been investigated in a variety of human tissues by immunohistochemistry and found to be widespread. , In humans, aside from the liver, AO activity has also been detected in excretory organs such as lung, the gastrointestinal tract, and kidney. In the gastrointestinal tract, AO activity resides primarily in the small and large intestine while in the respiratory system it is abundant in epithelial cells from the trachea and bronchium, as well as in alveolar cells.…”
Section: Tissue Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…AO distribution in other tissues is highly species dependent. For example, in mouse AO activity in lung tissue is more significant than in the rat. The distribution of AO at the cellular level has also been investigated in a variety of human tissues by immunohistochemistry and found to be widespread. , In humans, aside from the liver, AO activity has also been detected in excretory organs such as lung, the gastrointestinal tract, and kidney. In the gastrointestinal tract, AO activity resides primarily in the small and large intestine while in the respiratory system it is abundant in epithelial cells from the trachea and bronchium, as well as in alveolar cells.…”
Section: Tissue Distributionmentioning
confidence: 99%
“…For example, in mouse AO activity in lung tissue is more significant than in the rat. [10][11][12] The distribution of AO at the cellular level has also been investigated in a variety of human tissues by immunohistochemistry and found to be widespread. 5,13 In humans, aside from the liver, AO activity *To whom correspondence should be addressed.…”
Section: Tissue Distributionmentioning
confidence: 99%
“…The involvement of aldehyde oxidases in the degradation of another vitamin, nicotinamide, is suggested by a number of studies on the ability of purified or enriched preparations of aldehyde oxidase from human [92], monkey [92], rat [93,94], rabbit [95] and guinea pig liver [96], and bovine eye [97] to oxidize N1-methylnicotinamide. For these reasons, animal aldehyde oxidases are included in the nicotinamide biochemical pathway (pathway: ko00760) of KEGG and are believed to catalyze the oxidation of N1-methylnicotinamide to N1-methyl-2-pyridone-5-carboxamide or N1-methyl-4-pyridone-5-carboxamide.…”
Section: Nicotinamidementioning
confidence: 99%
“…4,5) Several studies have demonstrated the presence of CYP enzymes and other metabolizing enzymes such as aldehyde oxidase in the ocular tissues, especially in the ciliary body of bovine and other experimental animals. [6][7][8] Previously, we have reported the characterization of CYP expression in rat ocular tissues and also reported the age-and gender-related expression patterns of the CYPs and phase II conjugation enzymes. 9,10) We have further reported the changes in the gene expression of drug metabolizing enzymes in Shumiya cataract rats (SCR) and seleniteinduced cataract rats.…”
Section: Introductionmentioning
confidence: 99%